(untitled) (Kronika Bydgoska, 2014)
The task of development of the concept and interior design with paintings and sculptures decorating the session room of the Municipal Council in the Bydgoszcz Council was given to the Museum Committee of the Municipal Museum. Plans included mounting of a big painting Collection of Duties on the Brda River in Bydgoszcz in the room, glorifying the commercial and industrial growth of the city in the 15th century, two replicas of portraits depicting Stanisław Staszic and Gen. Jan Henryk Dąbrowski, and a bas-relief of the coat of arms of the city combined with the national emblem. The most-attention grabbing object was a historical painting, for which a competition was announced. During selection of painters, the Museum Committee consulted people recognized as experts in the field of art (Feliks Kopera, PhD, Mieczysław Treter, PhD, Jan Skotnicki, and the Rev. Szczęsny Dettloff, PhD) as well as professors from the Academy of Fine Arts in Krakow and the School of Fine Arts in Warsaw. In the same time, the consultants were supposed to indicate the best copyists, who were supposed to be commissioned with making of replicas. Several outstanding painters with recognized accomplishments were invited to participate in the competition to make a sketch to historical painting, including Tadeusz Pruszkowski, Antoni Michalak, Michał Boruciński, Jan Henryk Rosen, and Jerzy Rupniewski. The jury was working on selecting one of the three sketches, choosing the drawing made by Antoni Michalak. Warsaw artists Janusz Podoski (Jan H. Dąbrowski) and Adam Rychtarski (Stanisław Staszic) were commissioned with making replicas of portraits. The last stage of work on the interior design of the session room was the city coat of arm competition, which invited Bydgoszcz sculptors - Roman Skręt, Piotr Triebler and Teodor Gajewski. Gajewski’s project was chosen. The crowning moment of interior design works was the exhibition of St. Luke’s Fraternity organized in the Bydgoszcz Municipal Museum. Organization of the competition appeared to be a great initiative of the local culture elites, blending in development of contemporary Polish art.